PESQUISA DE AUTOAVALIAÇÃO DO PROGRAMA DE PÓS GRADUAÇÃO EM CIÊNCIAS FARMACÊUTICAS DA UNIVERSIDADE ESTADUAL DO OESTE DO PARANÁ - Horvath, Barbara Sackser (2022)
To contribute to ensuring the quality of Brazilian graduate studies, CAPES implemented the Quadrennial Evaluation process of stricto sensu Graduate Programs, regulated by Ordinance N. 59 of March 21st, 2017. One of the assessed items included in the Quadrennial Evaluation is the elaboration of a mandatory institutional self-assessment plan. This self-assessment work aimed to monitor the quality of the Graduate Program in Pharmaceutical Sciences at UNIOESTE (PCF). To perform this research, the SWOT analysis (Strengths, Opportunities, Weaknesses and Threats) was used as a pedagogical tool for self-assessment diagnosis in a group of 158 participants, with the following characters: professors, students, dropout students, technical employees and former students. Subsequently, a self-assessment questionnaire was developed based on the results of the SWOT analysis and applied to the group of characters. The results obtained in this second stage of the research were submitted to descriptive statistical analysis, individually summarized through the percentages from the response options provided and in the assessment of agreement through the Likert scale. A comparative assessment between the groups was performed for each common question between them. The response matrices were converted into similarity measurements and analyzed using the principal coordinate ordering technique (PCoA). There was dispersion between the groups evaluated by the analysis of homogeneity (Permdisp), and by the analysis of the t and HSD Tukey tests, it was observed which answer options for each question were responsible for the dispersion of the data between the groups and of the central measures. There was similarity in the response of students and graduates and a certain dissonance in the response of professors, which suggests that the aspects of improvement need to be evaluated according to each group, as professors and students have evaluated the strengths and weaknesses of the PCF under different perspectives.